A prospective cohort study of postpartum glucose metabolic disorders in early versus standard diagnosed gestational diabetes mellitus - Valeria Cosma (Nature Portfolio, 2021)
Abstract Early gestational diabetes mellitus (eGDM) is diagnosed when fasting plasma glucose before 24 weeks of gestation (WG) is ≥ 5.1 mmol/L, whilst standard GDM is diagnosed between 24 and 28 WG by oral glucose tolerance test (OGTT). eGDM seems to have worse obstetric outcomes than standard GDM. We compared the rates of postpartum glucose metabolism disorders between women with early versus standard GDM in this prospective study on women with GDM from three university hospitals between 2014 and 2016. Patients were included if they were < 24 WG with at least one risk factor for GDM and excluded if they had type 2 diabetes. Patients were assigned to Group 1 (G1) for eGDM according to IADPSG: fasting blood glucose < 24 WG between 5.1 and 7 mmol/L. Group 2 (G2) consisted of patients presenting a standard GDM at 24–28 WG on OGTT results according to IADPSG: T0 ≥ 5.1 mmol/L or T60 ≥ 10.0 mmol g/L or T120 ≥ 8.5 mmol/L. The primary outcome was postpartum OGTT result. Five hundred patients were analysed, with 273 patients undergoing OGTT at 4–18 weeks postpartum: 192 patients in G1 (early) and 81 in G2 (standard). Patients in G1 experienced more insulin therapy during pregnancy than G2 (52.2% versus 32.5%, p < 0.001), but no patients were taking insulin postpartum in either group. G1 patients experienced less preterm labour (2.6% versus 9.1%, p = 0.043), more induced deliveries (38% versus 25%, p = 0.049) and reduced foetal complications (29.2% versus 42.0%, p = 0.048). There was no significant difference in the rate of postpartum glucose metabolism disorders (type 2 diabetes, impaired glucose tolerance, impaired fasting glycaemia) between groups: 48/192 (25%) in G1 and 17/81 (21%) in G2, p = 0.58. Thus the frequency of early postpartum glucose metabolism disorders is high, without difference between eGDM and standard GDM. This supports measurement of fasting plasma glucose before 24 WG and the threshold of 5.1 mmol/L seems appropriate until verification in future studies. Trial registration: NCT01839448, ClinicalTrials.gov on 22/04/2013.